2001
DOI: 10.1111/j.2042-7174.2001.tb01115.x
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of CPD within the pharmacy profession

Abstract: Focal points □ A questionnaire was used to determine current perceptions of continuing professional development within the pharmacy profession in Northern Ireland □ Although the majority of respondents understood the concept, few pharmacists currently practise this method of professional development □ Almost 90 per cent of responding pharmacists agreed/strongly agreed that it was essential for all practising pharmacists to participate in continuing professional development □ Lack of time, remuneration and locu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
55
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(70 citation statements)
references
References 0 publications
6
55
2
Order By: Relevance
“…[16][17][18] The practical effectiveness of this process is, however, called into question by this sample of pharmacists. Concerns exist about the way to document activities, a lessstructured and consequently less-rigorous approach than attendance-based approaches, and the ease with which CPD reporting might be faked.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] The practical effectiveness of this process is, however, called into question by this sample of pharmacists. Concerns exist about the way to document activities, a lessstructured and consequently less-rigorous approach than attendance-based approaches, and the ease with which CPD reporting might be faked.…”
Section: Discussionmentioning
confidence: 99%
“…A study carried out in 2001 aimed to discover perceptions of pharmacists in Northern Ireland on CPD. All pharmacists in Northern Ireland were sent a questionnaire (n = 1689; response rate 24%) and factors such as lack of time, remuneration, shortage of locum cover and lack of understanding of CPD were all identified as barriers to participation [8]. A further study by questionnaire sent to all pharmacists in one English region (n = 750; response rate 43%) evaluated the current practices of pharmacists with regard to their professional development and found that 90% of respondents had undertaken continuing education in the previous 12 months [9].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, when we compared different studies which determined the most important barriers in CE-or CPD-context, no major differences are observed. Time/job constraints, location, family responsibilities, relevance of courses and financial incentives are the most important barriers in both CE and CPD [6,8]. Further research needs to confirm the value of these results when implementing in a future CPD system.…”
Section: Discussionmentioning
confidence: 99%
“…Barriers in both CE and CPD, such as lack of time and motivation were found [1,[6][7][8]. Remuneration, locum cover and lack of understanding of CPD were also identified as barriers to participate in CPD [8].…”
mentioning
confidence: 99%
See 1 more Smart Citation